Fenologi Pembungaan dan Pembuahan pada Tumbuhan Rukam (Flacourtiar rukam Zoll. & Moritzi) - Juwita, Agustara Dwi; Robika, Robika; Akbarini, Dian (Biota, 2024)
Rukam is one of the fruiting plants that grow wild in the forest or are planted. Excessive utilization without cultivation efforts triggers a decrease in the population of a species in nature until a species disappears from nature. Flacourtia rukam has most recently been assessed for The IUCN Red List of Threatened Species in 2023. Flacourtia rukam is listed as Least Concern. Therefore, knowledge of flower and fruit development is needed to determine the effectiveness of production on rukam plants through phenological studies. This study was conducted to obtain information through morphological changes that occur and the length of time required during the flowering process to fruit formation on rukam. This research was conducted by directly observing and measuring the parts of the inflorescence from the process of fruit formation until the fruit ripenning. The results showed that the morphological structure of rukam flowers is incomplete. The phenology of rukam flowering and fruiting takes 56 - 61 days starting with the flower initiation phase and ending with the mature fruit phase. The stages of morphological changes in flower development can be divided into initiation, small flower buds, large flower buds, and blooming flowers (anthesis). While the stages of morphological changes in fruit, color and size can be divided into young fruit, mature fruit, ripe fruit, and deciduous fruit. All stages of color change occur during the fruit ripening process